Long Shelf‐Life Efficient Electrolytes Based on Trace l‐Cysteine Additives toward Stable Zinc Metal Anodes. Issue 37 (8th August 2022) - Huang, Cong; Zhao, Xin; Hao, Yisu; Yang, Yujie; Qian, Yang; Chang, Ge; Zhang, Yan; Tang, Qunli; Hu, Aiping; Chen, Xiaohua
Abstract: The unstable anode/electrolyte interface (AEI) triggers the corrosion reaction and dendrite formation during cycling, hindering the practical application of zinc metal batteries. Herein, for the first time, l ‐cysteine (Cys) is employed to serve as an electrolyte additive for stabilizing the Zn/electrolyte interface. It is revealed that Cys additives tend to initially approach the Zn surface and then decompose into multiple effective components for suppressing parasitic reactions and Zn dendrites. As a consequence, Zn|Zn symmetric cells using trace Cys additives (0.83 mm ) exhibit a steady cycle life of 1600 h, outperforming that of prior studies. Additionally, an average Coulombic efficiency of 99.6% for 250 cycles is also obtained under critical test conditions (10 mA cm −2 /5 mAh cm −2 ). Cys additives also enable Zn–V2 O5 and Zn–MnO2 full cells with an enhanced cycle stability at a low N/P ratio. More importantly, Cys/ZnSO4 electrolytes are demonstrated to be still effective after resting for half year, favoring the practical production. Abstract : An efficient electrolyte with a long shelf life is successfully prepared by adding trace l ‐cysteine (Cys) additives into 2 m ZnSO4 solution. It is demonstrated that a robust solid electrolyte interphase layer (SEI) is formed on the Zn surface due to the decomposition of Cys, which endows Zn anodes with superior cycle stability at practical test conditions.